2002
DOI: 10.1083/jcb.200110161
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent resonant energy transfer–based biosensor reveals transient and regional myosin light chain kinase activation in lamella and cleavage furrows

Abstract: Approaches with high spatial and temporal resolution are required to understand the regulation of nonmuscle myosin II in vivo. Using fluorescence resonance energy transfer we have produced a novel biosensor allowing simultaneous determination of myosin light chain kinase (MLCK) localization and its [Ca2+]4/calmodulin-binding state in living cells. We observe transient recruitment of diffuse MLCK to stress fibers and its in situ activation before contraction. MLCK is highly active in the lamella of migrating ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 47 publications
(81 reference statements)
10
81
0
Order By: Relevance
“…There is strong evidence supporting the importance of ROCK as well as MLCK during cytokinesis (Poperechnaya et al, 2000;Matsumura et al, 2001;Chew et al, 2002;Matsumura, 2005). However, we find that although both signaling mechanisms are required for cytokinesis, they are required at different times.…”
Section: Signaling Pathways Regulating Myosin II Activationmentioning
confidence: 47%
See 1 more Smart Citation
“…There is strong evidence supporting the importance of ROCK as well as MLCK during cytokinesis (Poperechnaya et al, 2000;Matsumura et al, 2001;Chew et al, 2002;Matsumura, 2005). However, we find that although both signaling mechanisms are required for cytokinesis, they are required at different times.…”
Section: Signaling Pathways Regulating Myosin II Activationmentioning
confidence: 47%
“…Studies of cylindrical sea urchin eggs suggested the presence of a molecular switch that signals the onset of cytokinesis and which is activated at the metaphase-anaphase transition (Shuster and Burgess, 2002b). It is possible that this switch identified in earlier experiments is related to the rise in cortical contractility observed in our compression assays.There is strong evidence supporting the importance of ROCK as well as MLCK during cytokinesis (Poperechnaya et al, 2000;Matsumura et al, 2001;Chew et al, 2002;Matsumura, 2005). However, we find that although both signaling mechanisms are required for cytokinesis, they are required at different times.…”
mentioning
confidence: 47%
“…Similar approaches have been used to explore the regulated conformations of proteins, such as kinesin and myosin light chain kinase activation (40,41). Before testing our model on ␤-catenin, robust positive and negative control constructs were designed to assess whether predicted spatial relationships could be quantified and confirmed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because RLC kinases including MLCK [29,30], ROK [31,32], and citron kinase [33] are localized in cleavage furrows, and because regulation of RLC kinases could theoretically control RLC phosphorylation, MP regulation may not be essential for cytokinesis. It should be noted, however, that contractile rings are dynamic structures that must contract and, at the same time, disassemble during cytokinesis [34,35].…”
Section: Mypt1 In Cell Divisionmentioning
confidence: 99%